Crush it! : why now is the time to cash in on your passion - Vaynerchuk, Gary (HarperStudio, 2009)
"Do you have a hobby you wish you could do all day? An obsession that keeps you up at night? Now is the perfect time to take those passions and make a living doing what you love. In Crush it! Gary Vaynerchuk shows how to use the power of the Internet to turn your real interests into real businesses"--Provided by publisher.